THE PROBLEM OF TRANSLATING OFFICIAL STYLE NEOLOGISMS FROM FOREIGN LANGUAGES - Geldiyeva Khursandoy (Galaxy International Interdisciplinary Research Journal, 2021)
New words or neologisms are words that have just entered the language and have taken their place as a dictionary in the vocabulary of a particular natural language. Neologisms are the result of many innovative developments as a result of scientific and technological progress, economic and financial progress, and the use of information technology as an important tool in everyday life. This article provides information about the role of neologisms in the development and preservation of language, types of neologisms, neologisms used in the official style, new words in the Uzbek language.